Letramento literário de alunos e alunas de pedagogia: entre os instrumentos e a formação - Silva, Maria Juliana de Macêdo (Universidade Federal Rural do Semi-Árido, 2019)
The low indices of Reading comprehension presented by the Brazilian students from researches and evaluations as the Programme for International Student Assessment (PISA), Portraits of Reading in Brazil and the System of Evaluation of Basic Education (SAEB) that leads to reflections about the process of Reading formation of the students and the upcoming teachers of the Basic Education, once they are responsible for promoting the reading formation of these students that are submitted to the processes of evaluation already mentioned. Thus, the main aim of the study is to analyse the situation of the Reading comprehension standards of fictional narratives from students of Pedagogy. Its specific objectives: to identify the characteristics of the fictional narratives and its relation with the Reading formation, develop an instrument for diagnosis of the Reading comprehension of fictional narratives and identify the situation of the reading comprehension of these students of Pedagogy course. In this sense, to answer the aims of this assignment, this work comes from a research of blended methods, combining a quantitative and qualitative approach, leaded by the following question: What is the situation of reading comprehension of these students of Pedagogy course? In doing so, an instrument of evaluation was developed for diagnosing their Reading Comprehension of Fictional Narratives – COMPLEIN, by means of 5 steps, it is stated the situation of the reading comprehension of the subjects in question. It was adopted a theoretical referential conducted by means of authors such as Azevedo (2002, 2007); Colomer (2007); Pontes (2012); Pontes and Azevedo (2013) to discuss about reading formation ; Bettelheim (2012); Eco (1986, 1994, 2003); Lajolo (1994); Zilberman (2003), and to discuss about Literary Reading; Cosson (2009), Literary Literacy; Freire (2001, 2009, 2011), to discuss about teacher formation; Gil (2016); Marconi and Lakatos (2003); Richardson (2017), and to structure the methodological path. The results shown revealed inferior numbers to the study, respectively 231,71/500 e 312,94/500, and indicates a low Literary Reading comprehension of the researched students
Keywords: Leitura; Literatura; Letramento literário; Cloze; Formação docente; Reading; Literature; Literary literacy; Cloze; Teacher formation; MULTIDISCIPLINAR::ENSINO